Strengthening Climate Finance in Nigeria: Lessons from Rwanda - Osuji, Francisca Obiageli; Ajise, Oduwa Jennifer (NIU Journal of Climate Justice and Governance; Vol 12 No 1 (2026): NIU Journal of Climate Justice and Governance, Vol. 12 No. 1, June 2026, 2026)
Climate finance involves allocating funds from local, national, and international sources to support actions for mitigating, adapting, and building resilience to climate change. As a developing nation, Nigeria grapples with addressing challenges in meeting its climate objectives as spelt out in the United Nations Framework Convention on Climate Change (UNFCCC), the Paris Agreement and its Nationally Determined Contributions (NDCs). This paper investigates the problems of accessing global climate fund and achieving sustainable environment in Nigeria. The increasing climate risks—such as flooding, rising sea levels, record temperatures, and prolonged droughts—underline the urgency for access to global climate finance. The paper found a lack of finance, inability to create a direct access entity (DAE), lack of institutional capacity, and enabling environment for the private-public partnership as impediments to access global climate finance for resilient environment. As the largest economy in Africa, Nigeria stands at a crucial juncture where access to global climate finance can help drive sustainability. Increased access to finance is therefore essential to reach development goals and climate targets. It argues against sole reliance on global finance but harnessing domestic funds especially with private-public partnerships to achieve its NDCs. The paper recommends adopting Rwandan best practices in enhancing government accreditation to global funds, improving training and institutional capacity, and creating an enabling environment characterized by political stability and security. Ultimately, the paper argues that inclusive finance is the most effective way to distribute climate resources to the grassroots level, enabling a just transition and comprehensive global climate action. Keywords: Climate Finance, Climate Risks, Sustainable Environment, Direct Access, Domestic Fund.